An analysis of political speeches on racism by president Donald Trump during his presidency - Alsaqer, Brooj Nasser Abdullah (Arab Journal for Sciences and Research Publishing, 2023)
This paper attempts to illuminate the ways in which racist ideology is represented and articulated in everyday discourse. Since racism has been and continues to be, a driving force behind segregation in the United States, American rhetoric has been selected as the data for this investigation. This research analyses the speeches of US President Donald Trump on racism towards Muslim people through linguistic, social, and cultural perspectives. The study is an attempt to cast light on the strategies that are used express racism in the President’s speeches. To achieve the research objectives, the researcher used the qualitative approach. The data was collected from six major speeches on racism made by President Donald Trump and downloaded from YouTube and the Euronews Arabic online channel. Fairclough model (1995) is used as the main analysis model in this research. The results show that the self-other schema was heavily evident in Trump's speech, in which he effectively portrayed himself as a national hero who wants to rescue America from suffering and disaster while painting Muslims in a bad light. This study also revealed Trump's transparent effort to promote his virtuous persona by using a number of rhetorical methods meant to instill undesirable traits to Muslims, such as pronounced Islamophobia. The results show that Trump utilizes demagogic language to establish a gap between Muslims and Americans, which he then uses to metaphorically exclude individuals of other ethnic identities, particularly Muslims.
Keywords: Political speeches; analysis; borrowing; President Donald Trump; racism